Performance Optimization of Strengthened Slab-on-Pile Structure with Braced Frame - Muhammad Firman Hidayat; Ali Awaludin; Bambang Supriyadi (Institute of Research and Community Outreach - Petra Christian University, 2024)
Slab-on-pile (SOP) have been constructed widely in many highway projects in Indonesia as it is preferable in soft-soil sites. This study is aimed to determine the optimal structural configuration by adding braced frame devices to the longitudinal direction of the slab-on-pile structure. The optimization process was carried out to obtain the minimum number of pile configurations, reducing construction costs. A total of three numerical models were compared, namely SOP-A, SOP-B, and SOP-C, representing SOP with configurations of 50 piles, 35 piles, and 35 piles plus thirty braced frames, respectively. The cyclic analysis procedure and structure design were executed based on ACI 374.1 and the Indonesian standard SNI 1725:2016. The results showed that all P-M responses of the SOP-A and SOP-C structures met the cross-section capacity requirements, except for the SOP-B. The addition of braced frames in SOP-C facilitated a 38% energy dissipation improvement and caused a significant reduction of number of the spun piles.